Direct Reprogramming of Mouse Fibroblasts into Functional Osteoblasts. (30th December 2019) - Zhu, Hui; Swami, Srilatha; Yang, Pinglin; Shapiro, Frederic; Wu, Joy Y.
ABSTRACT: Although induced pluripotent stem cells hold promise as a potential source of osteoblasts for skeletal regeneration, the induction of pluripotency followed by directed differentiation into osteoblasts is time consuming and low yield. In contrast, direct lineage reprogramming without an intervening stem/progenitor cell stage would be a more efficient approach to generate osteoblasts. We screened combinations of osteogenic transcription factors and identified four factors, Runx2, Osx, Dlx5, and ATF4, that rapidly and efficiently reprogram mouse fibroblasts derived from 2.3 kb type I collagen promoter‐driven green fluorescent protein (Col2.3GFP) transgenic mice into induced osteoblast cells (iOBs). iOBs exhibit osteoblast morphology, form mineralized nodules, and express Col2.3GFP and gene markers of osteoblast differentiation. The global transcriptome profiles validated that iOBs resemble primary osteoblasts. Genomewide DNA methylation analysis demonstrates that within differentially methylated loci, the methylation status of iOBs more closely resembles primary osteoblasts than mouse fibroblasts. We further demonstrate that Col2.3GFP + iOBs have transcriptome profiles similar to GFP + cells harvested from Col2.3GFP mouse bone chips. Functionally, Col2.3GFP + iOBs form mineralized bone structures after subcutaneous implantation in immunodeficient mice and contribute to bone healing in a tibia bone fracture model. These findings provide an approach to derive and study osteoblasts for skeletal regeneration. © 2019 American Society for Bone and Mineral Research.